HUBUNGAN DAYA TARIK JINGLE IKLAN DAN DAYA TARIK CELEBRITY ENDORSER SAL PRIADI DENGAN BRAND IMAGE IM3 OOREDOO (STUDI EKSPERIMEN PADA IKLAN “BULAN YANG BAIK”) - Nanda Immanuella; Agus Naryoso; Amida Yusriana (Interaksi Online, 2023)
Advertising is an important element of a series of product promotions that has an impact on how the brand image is perceived in the consumer's brain. IM3 Ooredoo uses advertising jingle and celebrity endorser Sal Priadi entitled "Bulan Yang Baik " in its advertising. IM3 Ooredoo continues to improve network quality from August 2021 until the end of 2022. However, the data shows IM3 Ooredoo's Top Brand Index has decreased and IM3 Ooredoo is in second place under Telkomsel as well as the number of subscribers. This study aims to determine whether there is a correlation between the attractiveness of advertising jingles and the attractiveness of celebrity endorser Sal Priadi with IM3 Ooredoo's brand image. Advertising Exposure Theory and Source Attractiveness Model Theory are used to explain the influence between variables. The sample is 30 respondents aged 15-25 years who actively use internet services based on nonprobability sampling and purposive sampling techniques. The type of research used is quantitative with the experimental research method pre-experimental design with one group pretest and posttest design.The results of the Wilcoxon Signed-Rank Test stated that there was a correlation between the attractiveness of advertising jingles and the attractiveness of celebrity endorser Sal Priadi with IM3 Ooredoo's brand image with Asymp. Sig (2-tailed) is 0.002 which is below 0.005.